Export Performance of Indonesian Manufactured Goods in Australia - Adnan, Muhammad Akhyar (The International Journal of Accounting and Business Society, 1993)
Export Performance of Indonesian Manufactured Goods in Australia The exports of Indonesian manufactured products to Australia are performing poorly, even if compared to those of Malaysia and Thailand. The objectives of this study is to investigate the factors behind the poor export performance of Indonesian manufactured products in Australia. Two types of research techniques were conducted. Firstly a literature review, which includes the study of the theoretical framework of international trade, previous related research results and collecting secondary data from various sources. These techniques were used to investigate the causal factors from a macro or general point of view. Secondly, mail survey. Two types of questionnaire were designed, one was forwarded to seventy eight Australian importers, and the other was sent to seventy eight Indonesian exporters. These were aimed at investigating the factors behind the problems from a micro or specific point of view. In addition, two interviews were conducted, first with the Indonesian Commercial Attache4 in Canberra, and second with the Director of Indonesian Commercial Office in Sydney. Descriptive and qualitative analysis was applied to major parts of the data obtained, with statistical manipulations applied to the remainder. T-statistic or student test as well as analysis of variance (ANOVA), F-test and orthogonal contrast test were applied to test the significances.The information collected indicates that macro aspects, such as communication problems, Indonesian banking practices, lack of information and shipment seem to play a more significant role in the poor export performance of Indonesian manufactured products to Australia than did the micro or specific aspects like the price and the quality of products. Keywords: Export; Indonesia; Manufactured Goods; Australia.